THE PROFESSIONAL THINKING FUTURE DIRECTED BY THEATRICAL PERFORMANCES AND HOLIDAYS: RESULTS OF EXPERIMENTAL WORK - Elena G. Protsenko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The author presents the results of the comparative analysis, and the formative experiment, based on the system developed for the formation of professional thinking at the future directors of theatrical performances and holidays. Testing of the proposed system was carried out on the basis of the Samara State Institute of Culture, the sample were third-year students majoring 70209.65 Directing theatrical performances and holidays, specialty "Directing concert and entertainment programs and traditional festivities". It is shown that in the course of formation of professional thinking at the future directors of theatrical performances and holiday’s task was carried out to form the components of professional thinking in the communicative, reflexive, cognitive, creative and procedural components. The selection means of formation of professional thinking at the future directors of theatrical performances and holidays carried out taking into account the specific nature of their professional activity. Specificity is also in the process of learning, dominated by special system of exercises to master acting skills; creativity and problem tasks aimed at addressing the research, design, communication and organizational tasks; role play, artistic and pedagogical situations that simulate the behavior of a director in the theater team. Game-interactive technologies identified by the author as the most effective means of providing training, allowing to realize the variety of objectives, contents, methods of teaching students in the classroom for special course "Psycho-pedagogical bases of assembly thinking formation of stage directors" of future directors of theatrical performances and holidays. Results of the study showed that at all stages it is advisable not to use certain means, methods and techniques aimed at the formation of certain components of professional thinking, and as a whole in accordance with the situation in which all parties are represented in its cooperation and unity. Forming experiment whose purpose was testing system formation of professional thinking at the future directors of theatrical performances and holidays, con-firmed its efficiency: marked by positive dynamics of formation of professional thinking.